Laços de família: a construção de uma comunidade de afeto no Programa Jairo Maia - Fraga, Katia de Lourdes (2005)
The main objective of the present research it discussing the construction of na affective community, which consolidates itself through the relationship between the listener and the radio Professional, having the speech as the central element of mediation and identity development, taking into consideration the parts played by each other, with the public s agreement. Therefore, identification connections built in a consolidated family around Jairo Maia Programme, which has been presented for 44 years on radio stations in Espirito Santo State, are analyzed.